PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM DENGAN PENGUNGKAPAN CSR SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Peusahaan Makanan dan Minuman yang Terdaftar di BEI Tahun 2014-2019) - Nabila Salsabila; Marsono Marsono (Diponegoro Journal of Accounting, 2022)
The purpose of this study is to test whether there is an effect of financial performance on stock price by involving the disclosure of corporate social responsibility (CSR) as a moderating variable. The results shown by this research are expected to help investors in making decisions when considering things to invest in the capital market. The company's financial performance is one of the factors that is still a mainstay in investment considerations. Financial performance can be assessed by conducting a fundamental analysis which will then be linked to its effect on stock price.Financial performance is measured using financial ratios represented by 4 ratios, namely ROE (Return On Equity), NPM (Net Profit Margin), Sales Growth, and DPR (Dividend Payout Ratio). This study uses quantitative research with secondary data, namely financial statements taken from the official website of the Indonesia Stock Exchange and related companies. The sample used is food and beverage companies listed on the IDX in 2014-2019, selected using a purposive sampling technique so that from 32 food and beverage companies listed on the IDX, 7 companies are obtained that meet the criteria.The analytical method used to test the hypothesis is multiple linear regression and MRA (Moderate Regression Analysis). The partial test shows that the significance value of ROE, NPM, and DPR is less than 0.05 indicating an effect on stock price, while the significance value of Sales Growth of more than 0.05 indicates no effect on stock price. The results of the moderation test show that the significance value of ROE that has been interacted with CSR disclosure and NPM that has been interacted with CSR disclosure is less than 0.05 indicating that CSR disclosure is able to moderate the effect of ROE and NPM on stock price, while the significance value of Sales Growth and DPR which has been interacted by CSR disclosure is more than 0.05. shows that CSR disclosure is not able to moderate the influence of Sales Growth and DPR on stock price.